Acute Human Immunodeficiency Virus (HIV) Syndrome After Nonadherence to Antiretroviral Therapy in a Patient With Chronic HIV Infection: A Case Report. (23rd December 2014) - Choi, Seong K.; Graber, Christopher J.
Abstract: We report a rare case of acute human immunodeficiency virus (HIV) syndrome in a patient with chronic HIV infection with acute illness indistinguishable from acute retroviral syndrome. The patient presented with an acute febrile mononucleosis-like illness after increasing nonadherence to antiretroviral therapy. A marked increase in HIV RNA level of 1 220 000 copies/mL from less than 20 copies/mL occurred within 3 weeks. The diagnosis of acute HIV syndrome was made after alternative causes of illness were ruled out.